Digital Media side by side with PAI Learning: Adaptation strategies in the digitalization period - Taufik Firdaus, Moh. (Saba Jaya Publisher, 2023)
This research departs from the strategy that teachers use in carrying out learning during the Covid-19 pandemic, namely distance learning (PJJ) so that it can run effectively, efficiently, and optimally and can run well. So, this study to show that Digital Media side by side with PAI Learning: Adaptation strategies in the digitalization period. This study uses a descriptive qualitative approach. The research subjects were one teacher of Islamic Religious Education (PAI) class IX, the principal informant and 20 students of class IX. Data collection techniques: observation, documentation and interviews. Data validation technique: triangulation technique. Data analysis techniques: data reduction (data selection), data display (data presentation) and conclusion drawing/verification (drawing conclusions). The results of the study show that: (1) Islamic Religious Education with its strategy in dealing with digitalization (2) Digital media has a good role in the continuity of learning